Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2017)
Light harvesting donor-acceptor assemblies are indispensable to efficiently tap photons. In an attempt to improve the light harvesting efficiency of an acceptor doped assembly, we design and synthesize a donor-acceptor-donor triad which exhibits an exceptional intramolecular energy transfer with excellent efficiency. Moreover, a facile cascade energy transfer (energy funnelling) is observed in the presence of a series of second acceptors (63-91% efficiency) with tunable emission colours. Self-assembled nanosheets formed by the triad in the presence of acceptors exhibit cascade energy transfer assisted tunable emission. In addition, use of chiral acceptors induces chirality to the triad and results in the formation of chiral nanosheets alongwith cascade energy transfer. Here chiral induction, nanosheet formation and cascade energy transfer in the presence of chiral acceptors are used as tools to probe the intercalation of acceptor molecules in the donor scaffold.

Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping (vol 53, pg 7072, 2017) - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Correction for `Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping' by Goudappagouda et al., Chem. Commun., 2017, 53, 7072-7075.

Charge transfer liquid: a stable donor-acceptor interaction in the solvent-free liquid state - Wakchaure, Vivek Chandrakant; Pillai, Lekshmi, V; Goudappagouda; Ranjeesh, Kayaramkodath Chandran; Chakrabarty, Suman; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Charge-transfer complexes have been an inspiration to develop many functional soft materials. However, most of those studies have focused on solution based assemblies wherein the explicit control of solvents and their polarity are crucial. In this context, we explore an efficient and stable charge transfer liquid using a solvent-free liquid dialkoxynaphthalene donor and a naphthalenediimide acceptor. It has been observed that irrespective of the donor-acceptor ratio, the charge-transfer liquid exhibited an unprecedented stability and retained characteristic features even at increased temperatures. The underlying intermolecular interactions leading to efficient CT have been examined by NMR techniques together with theoretical modelling studies. The concept of charge transfer liquid will be highly beneficial for the development of processable optoelectronically active materials.

Imidazole-linked crystalline two-dimensional polymer with ultrahigh proton-conductivity - Ranjeesh, Kayaramkodath Chandran; Ilathvalappil, Rajith; Veer, Sairam Dnyaneshwar; Peter, Joseph; Wakchaure, Vivek Chandrakant; Goudappagouda; Raj, K. Vipin; Kurungot, Sreekumar; Babu, Sukumaran Santhosh (Journal of the American Chemical Society, 2019)
Proton-exchange membrane fuel cells are promising energy devices for a sustainable future due to green features, high power density, and mild operating conditions. A facile proton-conducting membrane plays a pivotal role to boost the efficiency of fuel cells, and hence focused research in this area is highly desirable. Major issues associated with the successful example of Nafion resulted in the search for alternate proton conducting materials. Even though proton carrier loaded crystalline porous organic frameworks have been used for protonconduction, the weak host-guest interactions limited their practical use. Herein, we developed a crystalline 2D-polymer composed of benzimidazole units as the integral part, prepared by the condensation of aryl acid and diamine in polyphosphoric acid medium. The imidazole linked-2D-polymer exhibits ultrahigh proton conductivity (3.2 X 10(-2) S cm(-1)) (at 95% relative humidity and 95 degrees C) in the pristine state, which is highest among the undoped porous organic frameworks so far reported. The present strategy of a crystalline proton-conducting 2D-polymer will lead to the development of new high performing crystalline solid proton conductor.

Durable metalloporphyrin 2D-polymer for photocatalytic hydrogen and oxygen evolution from river and sea waters - Ranjeesh, Kayaramkodath Chandran; George, Leena; Maibam, Ashakiran; Krishnamurty, Sailaja; Babu, Sukumaran Santhosh (ChemCatChem, 2021)
It is highly imaginary that the outcome of a combination of two complementary resources leads to answer an alarming global issue. One such possible example is the solar seawater splitting for `clean fuel' H-2 generation. Since the catalytic activity and stability of the photocatalysts are substantially challenged in seawater, the design of an efficient and stable photocatalyst is highly desirable. Herein, we demonstrate the solar seawater splitting by a two-dimensional polymer catalyst derived from metalloporphyrin bearing multi-hydroxyl groups. A bimetallic (Co and Ni) porphyrin 2D-polymer exhibits excellent long-term durability of 15 cycles of H-2 and O-2 generation in 200 days from pure water without a considerable decrease in efficiency. Detailed studies using river and seawaters also show the reliable performance of the catalyst over repeated cycles. Here the deactivation modes of catalytic activity have been nullified by the layered metalloporphyrin polymer structure through stable pi-pi stacking, signifying the molecular design of 2D-polymer photocatalyst.
Keywords: 2D-polymer; Photocatalyst; porphyrin; Self-assembly; water splitting

Heteroatom-synergistic effect on anchoring polysulfides in chalcone-linked nanographene covalent organic frameworks for high-performance Li―S batteries - Ranjeesh, Kayaramkodath Chandran; Javaregowda, Bharathkumar H.; Gaber, Safa; Bhauriyal, Preeti; Kumar, Sushil; Skorjanc, Tina; Finsgar, Matjaz; Heine, Thomas; Krishnamoorthy, Kothandam; Shetty, Dinesh (Advanced Science, 2025)
Lithium-sulfur (Li & horbar;S) batteries are an attractive option for future energy storage devices because they offer higher theoretical specific capacity, energy density, and cost-effectiveness than commercial lithium-ion batteries. However, the practical applications of Li & horbar;S batteries are significantly limited by the shuttle effect caused by intermediate lithium polysulfides (LiPSs) and slow redox kinetics. In this study, the molecular engineering of chalcone-linked, sp(2)-bonded nanographene-type covalent organic frameworks (COFs) as sulfur hosts is reported to enhance interactions with LiPSs, thereby effectively suppressing the shuttle effect. The developed sulfur-hosting cathode material demonstrated outstanding battery performance, surpassing most reported materials by achieving a specific capacity of 1228 mA h g(-1) at 0.5C, with 80% retention after 500 cycles and an average Coulombic Efficiency (C.E.) of 99%. Additionally, the mechanisms of sulfur immobilization, the subsequent conversion into lithium polysulfides (LiPSs), and their binding energies with COFs are investigated using density functional theory (DFT) calculations. These findings offer valuable insights into the structure-property relationships essential for developing more efficient sulfur-hosting cathodes.
Keywords: anion-pi interaction; covalent organic frameworks; lithium-sulfur battery; nanographene; polysulfide shuttle